Necesidad de un proyecto de ley para la migración de la amplitud modulada (AM) a la frecuencia modulada (FM) (2014)
The disappearance of the frequency-modulated broadcast AM is imminent. This threatens to extinguish the country construction that is performed through radio stations transmitting with AM frequency. AM frequency has lower signal quality and lower capacity to transmit large amount of content, and devices for transmission and reception of AM are no longer produced. Meanwhile, the FM frequency is higher quality although and coverage. However it houses almost 80 illegal stations and it is believed that FM frequency has no more space in the spectrum. In this paper, the need to protect stations in AM through creation a legislation regulating the migration of AM to FM stations is exposed; for it would be necessary to eliminate illegal broadcasters which would free up spectrum space and regulate competition preventing the creation of monopolies